Jelly beans for sale - McMillan, Bruce (New York : Scholastic, 1996)
Shows how different combinations of pennies, nickels, dimes, and quarters can buy varying amounts of jelly beans. Includes information on how jelly beans are made.
Wilson's Children
Notable/Best Books (A.L.A.)
School Library Journal
1.3
K-3
Keywords: Addition -- Juvenile literature; Coinage -- United States -- Juvenile literature; Jellybeans -- Juvenile literature; Addition; Coins; Money; Jellybeans; Addition; Coins; Money; Jellybeans